Genyadana : - Scott, A. C. (The Hokuseido Press, 1953)
Kabuki is the most popular form of Japanese traditional theatre, a colourful and exciting spectacle based on traditional, historical and mythic narratives, many of which involve the code of the samurai. Dazzling though the costumes and makeup are, Kabuki is basically the telling of a story, but as there is no spoken narrative or dialogue in Kabuki, the story has to be known in advance, in order to fully appreciate the performance. A proper playgoer's companion, it not only gives plot summaries of more than a hundred of the greatest and best Kabuki plays and dances, but also describes exactly what is happening on stage as the performance proceeds -- who the characters are, how they can be identified, when they enter and exit, and what they are doing. All forms of Kabuki drama are included -- exotic spectacles, classical plays about valour and devotion, love stories and dances. The structure of Kabuki programmes is explained, as are the technical terms and customs that visitors find perplexing, and there is a helpful system of cross referencing, and a comprehensive index. It enables novices to appreciate the unique art of Kabuki for the first time, and enhances the appreciation of experts. Indispensable for any play-goer, this remarkable volume is also a valuable resource for all students of traditional Japanese culture and literature